Multikulturalisme dan Politik Identitas: Catatan Reflektif atas Gagasan Politik Will Kymlicka - Amsar A. Dulmanan (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2020)
Diversity is a sociological fact of the Indonesian that cannot be denied. Diversity is the innate origin of the Indonesian nation, even long before the Indonesian nation-state was formed. It means, traditionally, the Indonesian people have actually been accustomed to diversity. But in the context of the modern Indonesian nation-state, diversity has meaning and socio-political demands that are far different from the ancient type of diversity. In this context, this article will discuss the political ideas of multiculturalism proposed by Will Kymlicka. Using the literature study this article discusses several views on multiculturalism, as well as the main points and general framework of Kymlicka’s multicultural political ideas and their position in the discourse on democracy and plural society. I argue that there are at least two dilemmas faced by theories of multiculturalism in looking at culture and cultural differences. First, an essentialist understanding of culture that presupposes that culture is a fixed, unchanging, and independent entity. Secondly the strong claims of university values in various understandings about multiculturalism is a challenge in itself, at the same time it indicates a long way to go in formulating theories to overcome the problem of cultural differences on the basis of the principle of liberalism.